2014
DOI: 10.1364/ol.39.003732
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced resonance of nanoparticle-loaded microbubbles

Abstract: We report on the optical excitation and detection of resonant microbubble oscillations. Optically absorbing nanoparticles were attached to the shell of a lipid-encapsulated microbubble, allowing for optical pulsing to photothermally drive the microbubble into resonance. A modified optical microscope was used to track the bubble wall radius as a function of time using light scattering. The microbubble response from a nanosecond laser pulse was measured, and the eigenfrequency and vibrational amplitude were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 22 publications
6
41
0
Order By: Relevance
“…Here, the bubble diameter was 3.56 µm and the measured resonant frequency was 2.67 MHz, giving a shell elasticity of 0.41 N/m. The shell elasticity is within the range, but on the lower side, of previously reported values [28]. Based on the measured bubble response one can conclude that the vaporized droplet retains a lipid shell with attached nanoparticles.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Here, the bubble diameter was 3.56 µm and the measured resonant frequency was 2.67 MHz, giving a shell elasticity of 0.41 N/m. The shell elasticity is within the range, but on the lower side, of previously reported values [28]. Based on the measured bubble response one can conclude that the vaporized droplet retains a lipid shell with attached nanoparticles.…”
Section: Resultssupporting
confidence: 73%
“…We do note that a small amount of bubble growth was observed at later times (several seconds) most likely due to gas efflux and influx of the core [26,27]. We have previously shown that nanoparticle-loaded microbubble oscillations can be induced by a pulsed laser source, and that the photoacoustic response from such microbubble populations exceeds that from free nanoparticles at the same nanoparticle concentration [22,28]. The microbubbles produced post vaporization remain optically active, indicating that the nanoparticles are not purged during the explosive vaporization of the droplet core.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Stable microbubbles modified with the addition of an optically absorbing coating have been proposed as a potential solution to this problem. 10,11 This is an attractive approach since gas bubbles are well established as contrast agents for ultrasound imaging. [12][13][14][15] In this case, the microbubble oscillations are stimulated by the heating and cooling of the coating and subsequently of the gas core upon optical irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The bubble coating can be loaded with light-absorbing particles 112 or a lowviscosity oil containing an absorbing dye (Cha. 8).…”
Section: Light Absorbing Microbubblesmentioning
confidence: 99%